Application of Think Pair Share Type Cooperative Learning Model to Improve Creative Thinking Ability - Firja MKS, Meyronita (CV. Tripe Konsultan, 2024)
This research aims to determine the effect of the Think pair share (TPS) cooperative learning model in improving the critical and creative thinking abilities of class VI C students at SD Negeri 1 Harapan Jaya. The classroom action research method used includes initial reflection, action plan, action, observation, evaluation, and final reflection. The results of the research were concluded as follows: (a) Students' critical thinking skills experienced an increase after the implementation of the Think Pair Share cooperative learning model by looking at the learning outcomes scores in the mathematical learning achievement. (b) Mathematics result scores of class VI C students at SD Negeri 1 Harapan Jaya experienced an increase after giving action. In the first cycle of students who had a score of 75-100, there were 21 students out of 30 students, while the second cycle of students had a score of 75-100 a total of 28 students out of 30 students. had success with a percentage of 93.33% and as many as 28 students. (c) Mathematics grade level of students in class VI C of SD Negeri 1 Harapan Jaya is increasing. Cycle I pada has completeness with a percentage of 70%, while cycle II has completeness with a percentage of 93.33%. (d) Students' ability to think creatively experiences an increase after the implementation of the Think Pair Share cooperative learning model by looking at the results of observations carried out during ongoing learning activities. In conclusion, the TPS learning model is effective in improving students' critical and creative thinking abilities. Therefore, teachers are recommended to adopt this method in teaching mathematics to achieve optimal results.